2010
DOI: 10.1099/ijs.0.013995-0
|View full text |Cite
|
Sign up to set email alerts
|

Haloterrigena daqingensis sp. nov., an extremely haloalkaliphilic archaeon isolated from a saline–alkaline soil

Abstract: A haloalkaliphilic archaeon, strain JX313T , was isolated from a saline-alkaline soil from Daqing, Heilongjiang Province, China. Its morphological, physiological and biochemical features and 16S rRNA gene sequence were determined. Colonies of the strain were orange-red and cells were non-motile cocci and Gram-stain-variable. The strain required at least 1.7 M NaCl for growth, with optimal growth occurring in 2.0-2.5 M NaCl. Growth was observed at 20-50 6C and pH 8.0-10.5, with optimal growth at 35 6C and pH 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…Several recent studies on the composition of soil microbial diversity in saline soils revealed that soil salinization had negative effects not merely on soil biochemical properties, but also on the structure of microbial communities (Foti et al, 2007;Yuan et al, 2007;Hidri et al, 2013;Wang et al, 2014;Zhang et al, 2015). Regarding the soil microbial community in saline soils of Songnen Plain, only some representative new species of halophilic and halotolerant bacteria and archaea have been reported by pure culture methods (Wu et al, 2008;Wang et al, 2010;Liu et al, 2011b;He et al, 2014;Pan et al, 2016). These microorganisms have gradually formed adaptations, including unique structures and physiological functions, such as the accumulation of osmotic adjustment-related substances (Yan and Marschner, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies on the composition of soil microbial diversity in saline soils revealed that soil salinization had negative effects not merely on soil biochemical properties, but also on the structure of microbial communities (Foti et al, 2007;Yuan et al, 2007;Hidri et al, 2013;Wang et al, 2014;Zhang et al, 2015). Regarding the soil microbial community in saline soils of Songnen Plain, only some representative new species of halophilic and halotolerant bacteria and archaea have been reported by pure culture methods (Wu et al, 2008;Wang et al, 2010;Liu et al, 2011b;He et al, 2014;Pan et al, 2016). These microorganisms have gradually formed adaptations, including unique structures and physiological functions, such as the accumulation of osmotic adjustment-related substances (Yan and Marschner, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…sedeminis also represents a novel genus within subclade 6E. The co-location of Haloterrigena daqingensis (Wang et al, 2010) with Nr. sedeminis (Fig.…”
mentioning
confidence: 94%
“…Since halophilic enzymes from the haloarchaea are generally considered to be active and stable at high salt concentrations, they have potential for biotechnological applications such as engineering for salt-resistant plants in agriculture, environmental bioremediation of organic pollutants and production of fermented foods. The genus Haloterrigena was first proposed by Ventosa et al [ 4 ] with the reclassification of Halococcus turkmenicus as Haloterrigena turkmenica [ 4 ], and presently includes nine species: H. turkmenica [ 4 ], H. thermotolerans [ 5 ], H. longa , H. limicola [ 6 ], H. saccharevitans [ 7 ], H. hispanica [ 8 ], H. jeotgali [ 9 ], H. salina [ 10 ], and H. daqingensis [ 11 ], all of which are pleomorphic, Gram-negative staining, and red- or light pink-pigmented. However, the genus Haloterrigena is poorly characterized at the genome level.…”
Section: Introductionmentioning
confidence: 99%